Perancangan Automatic Drying Machine Dengan Metode Rasional - Ferida Yuamita; Adwiyah Asyifa; Ari Sugiharto (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
Effectiveness is the goal in a system. To achieve this, it is necessary to carry out continuous development. Likewise, what is done in small industries in Pasangsari village, Windusari district, Magelang regency. The abundance of cassava in this area makes the community required to innovate in terms of cassava processing. One of the speakers processes cassava into rengginang. By processing it into rengginang, the cassava has a longer life because it is stored in a dry state. In addition, selling cassava that has been processed into rengginang has greater added value in terms of selling price. The problem in this study is the effectiveness of the tool because it still uses conventional methods where the drying process is still dependent on sunlight, while erratic weather conditions become a barrier in the drying process. The purpose of this research is to design a tool with a temperature control system so that the effectiveness of the tool manufacturing process can be achieved. Keywords: automatic drying machine, design, production, cassava, rational methods